2001
DOI: 10.1091/mbc.12.11.3527
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle-dependent Expression and Nucleolar Localization of hCAP-H

Abstract: Condensin is a conserved 13S heteropentamer composed of two nonidentical structural maintenance of chromosome (SMC) family proteins, in Xenopus XCAP-C and XCAP-E, and three regulatory subunits, XCAP-D2, XCAP-G, and XCAP-H. Both biochemical and genetic analyses have demonstrated an essential role for the 13S condensin complex in mitotic chromosome condensation. Further, a potential requirement for condensin in completion of chromatid arm separation in early anaphase is demonstrated by the mutational phenotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 36 publications
6
42
0
Order By: Relevance
“…Most authors demonstrated diffuse distribution of SMC proteins throughout the nucleus (Saitoh et al, 1994;Hirano and Mitchison, 1994), whereas Journal of Cell Science 116 (9) others reported concentration of these proteins in discrete subnuclear domains of an unknown nature (Schmiesing et al, 1998). Recently, nucleolar localization of the human condensins hCAP-H has been reported (Cabello et al, 1999;Cabello et al, 2001). Similar results were obtained for S. cerevisiae, where GFP-tagged pSmc4 was shown to accumulate in the nucleolus prior to entry into mitosis (Freeman et al, 2000).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Most authors demonstrated diffuse distribution of SMC proteins throughout the nucleus (Saitoh et al, 1994;Hirano and Mitchison, 1994), whereas Journal of Cell Science 116 (9) others reported concentration of these proteins in discrete subnuclear domains of an unknown nature (Schmiesing et al, 1998). Recently, nucleolar localization of the human condensins hCAP-H has been reported (Cabello et al, 1999;Cabello et al, 2001). Similar results were obtained for S. cerevisiae, where GFP-tagged pSmc4 was shown to accumulate in the nucleolus prior to entry into mitosis (Freeman et al, 2000).…”
Section: Discussionmentioning
confidence: 77%
“…Taking into account the fact that intracellular levels of condensin subunits remain practically constant throughout the cell cycle [this study; (Schmeising et al, 1998;Cabello et al, 2001)], one should expect condensins to exert some yet unknown function(s) during interphase. It is a plausible hypothesis that condensins act as regulators of gene expression by controlling the accessibility of chromatin loci to transcription factors via local condensation/decondensation of interphase chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…In performing both of these roles, the cells seem to acquire a higher potential for stably maintaining long repeat structures; this is because replication fork blocking activity and condensin are conserved in various organisms. From this point of view, it is very interesting that condensin in human cells is concentrated in the nucleolus during the interphase (8). Further, in bacteria, both SMC-like proteins (e.g., that encoded by mukB in Escherichia coli) and replication fork blocking systems (Ter site and Tus protein) are found, and chromosome segregation defects were observed in mutants of SMC-related genes (6,19,21,22,37,39,53).…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of centromeric MCAK leads to chromosome congression and segregation defect due to improper kinetochore attachments (Kim et al, 1997;Sugata et al, 2000;KlineSmith et al, 2004). hCAP-H plays a central role in mitotic chromosome condensation (Cabello et al, 2001;Kimura et al, 2001). SRP1, the yeast homologous of KPNA2, has been shown to be critical for normal migration, division and integrity of nuclei during mitosis (Kussel and Frasch, 1995).…”
Section: An Expression Signature For Anaplastic Wilms Tumormentioning
confidence: 99%